Knockdown of Annexin-A1 Inhibits Growth, Migration and Invasion of Glioma Cells by Suppressing the PI3K/Akt Signaling Pathway. (March 2021) - Wei, Liqing; Li, Li; Liu, Li; Yu, Ru; Li, Xing; Luo, Zhenzhao
ANXA1, which can bind phospholipid in a calcium dependent manner, is reported to play a pivotal role in tumor progression. However, the role and mechanism of ANXA1 involved in the occurrence and development of malignant glioma are still not well studied. Therefore, we explored the effects of ANXA1 on normal astrocytes and glioma cell proliferation, apoptosis, migration and invasion and the underlying mechanisms. We found that ANXA1 was markedly up-regulated in glioma cell lines and glioma tissues. Down-regulation of ANXA1 inhibited normal astrocytes and glioma cell proliferation and induced the cell apoptosis, which suggested that the consequences of loss of Annexin 1 are not specific to the tumor cells. Furthermore, the siRNA-ANXA1 treatment significantly reduced tumor growth rate and tumor weight. Moreover, decreasing ANXA1 expression caused G2/M phase arrest by repressing expression levels of cdc25C, cdc2 and cyclin B1. Interestingly, ANXA1 did not affect the expressions of β-catenin, GSK-3β and NF-κB, the key signaling molecules associated with cancer progression. However, siRNA-ANXA1 was found to negatively regulate phosphorylation of AKT and the expression and activity of MMP2/-9. Finally, the decrease of cell proliferation and invasiveness induced by ANXA1 down-regulation was partially reversed by combined treatment with AKT agonist insulin-like growth factor-1 (IGF-1). Meanwhile, the inhibition of glioma cell proliferation and invasiveness induced by ANXA1 down-regulation was further enhanced by combined treatment with AKT inhibitor LY294002. In summary, these findings demonstrate that ANXA1 regulates proliferation, migration and invasion of glioma cells via PI3K/AKT signaling pathway.